Agências de classificação de risco e a dinâmica dos campos: trajetórias, capitais e a dominação financeira - Nascimento, Romário Rocha do (Universidade Federal de São Carlos, 2025)
Credit Rating Agencies [CRAs] are influential and powerful institutions in the international financial market able of impacting the economies of companies and sovereign states. Over the years, they have acquired financial, cultural, political, and economic resources, which have granted them a significant level of influence within the dominant core of the financial market—comprised of the State, banks, and global governance institutions. From this perspective, the objective of this thesis is to analyze how CRAs structure an influential position within the dominant core of the financial market. To achieve this goal, we have divided the research into three studies, each grounded in and structured by distinct objectives, propositions, and methods. The first paper employs the theory of fields to understand the inter-field relationship between the State and CRAs. Through historical documentary research, we analyze some of the key regulatory milestones and events involving CRAs in the financial market. The study highlights how the State engaged various other market fields to promote the legitimacy of CRAs’ performative work. The second paper examines the trajectory and capital accumulation by actors in the field of Agencies Moody’s and S&P— the two largest CRAs in the market. Using prosopography data analysis and Multiple Correspondence Analysis [MCA] the study identifies and assesses six forms of capital held by CRAs: commercial, social-organizational, economic-financial, technological, cultural, and symbolic. The study reveals through perceptual maps that the trajectory and capital accumulation by the actors defined the influential position of CRAs in the dominant core of the financial market, particularly through commercial, technological, and symbolic capital. The third article examines the role of financial innovation as a fundamental mechanism for restructuring the order and stability of the CRAs field. Based on a historical analysis of secondary data, a narrative of crisis recovery was constructed, emphasizing the role of financial innovations and how they function as containment mechanisms used by actors to reorganize the field’s order. We believe the three studies support the central thesis question. Furthermore, the thesis upholds a theoretical premise by offering, as an alternative, the relational analysis between economic sociology and market approaches to relativize a current critique concerning complex empirical problems and the lack of dialogue between disciplines. Thus, we discuss the complementarity between theory of fields and other approaches, such as performativity, market devices, and financial innovation. In this way, the research opposes a simplified view of markets and considers them as complex, intertwined entities, simultaneously connected to social relations and broader historical-cultural contexts.
Credit rating agencies and the dynamics of fields: trajectories, capitals and financial domination
Keywords: Agências de Classificação de Riscos; Governança global; Núcleo dominante; Teoria de campos; Credit Rating Agencies; Dominant core; Global governance; Theory of fields; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO